2018
DOI: 10.18553/jmcp.2018.24.7.608
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Aflibercept Versus Ranibizumab for Wet Age-Related Macular Degeneration: A Cost-Effectiveness Analysis

Abstract: This study was funded by Regeneron Pharmaceuticals, the manufacturer of aflibercept. Hernandez, Lanitis, Cele, and Toro-Diaz are employed by Evidera, which received funding from Regeneron Pharmaceuticals to conduct this study. Gibson and Kuznik are employed by and own stock in Regeneron Pharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
1
14
0
3
Order By: Relevance
“…One study using a similar Markov structure with on-treatment and off-treatment health states, and substates based on BCVA found that aflibercept was cost-effective compared with ranibizumab for the treatment of wet AMD. 51 The findings of this study are consistent with earlier analyses showing similar QALY gains with aflibercept and ranibizumab, with lower costs for aflibercept compared with ranibizumab.…”
Section: Discussionsupporting
confidence: 91%
“…One study using a similar Markov structure with on-treatment and off-treatment health states, and substates based on BCVA found that aflibercept was cost-effective compared with ranibizumab for the treatment of wet AMD. 51 The findings of this study are consistent with earlier analyses showing similar QALY gains with aflibercept and ranibizumab, with lower costs for aflibercept compared with ranibizumab.…”
Section: Discussionsupporting
confidence: 91%
“…ADVM-022 gene therapy has been designed to address the challenges associated with the current standard of care for nAMD, notably the repeated IVT injections for the lifetime of the patient required to maintain visual function, 30 , 31 by providing a continuous supply of an approved anti-VEGFA protein to the eye after a single IVT delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Per-dose cost is approximately US $772.94 per syringe, per pill, or unit, for pegaptanib; US $1216.65 per syringe, per pill, or unit for ranibizumab; US $1920.04 per vial, per pill, or unit, for aflibercept; and US $50 for bevacizumab. 6062 According to the model developed by Kuopio University Hospital, 63 the direct medical costs include: (a) the costs of diagnosis including medical visit, FA, and OCT; (b) the cost of intravitreal injection of the medication; (c) the costs of follow up, including a medical visit and OCT; and (d) rehabilitation of legally blind persons. For one patient, a 6-week regimen with pegaptanib costs US $7729.40 per year, while bevacizumab PRN costs US $1610.40, ranibizumab PRN costs US $16,687.70, bevacizumab monthly costs US $2924.60, ranibizumab monthly US $25,759.20, aflibercept monthly costs US $13,954.70, aflibercept bimonthly costs US $6977.3, bevacizumab treat-and-extend regimen costs US $2167.9, ranibizumab treat-and-extend regimen costs US $18,678.9, and afliber-cept treat-and-extend regimen costs US $11,280.1.…”
Section: Discussionmentioning
confidence: 99%